Tác động điều tiết của rủi ro cảm nhận đến mối quan hệ giữa chất lượng kết quả mua hàng và sự hài lòng của khách hàng đối với dịch vụ thương mại điện tử - Nguyen Thu , Ha (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2019)
Shopping through e-commerce websites is often considered to be a higher risk business form than traditional shopping. Although participating in the same e-commerce environment, the level of risk that each customer perceives is not the same, which may affect customer satisfaction when receiving purchase results with similar service quality. This paper focuses on clarifying the impact of perceived risks on the relationship between the outcome quality of web-based purchasing and customer satisfaction in Vietnamese e-commerce. The questionnaire survey was conducted and data from 315 customers who purchased at Shopee website recently was collected. The analysis results indicate that perceived risk has a moderating effect on the relationship between timeliness and customer satisfaction as well as the relationship between order accuracy and customer satisfaction. Based on the results of the analysis, the author provides various suggestions on future research directions and implications for e-commerce business managers in minimizing perceived risks, aiming to improve customer satisfaction on service quality.